Estudo da toxicidade de hidrocarbonetos monoaromaticos utilizando Vibrio fischeri, Daphnia magna e Desmodesmus subspicatus - Berton, Silvia Mara Haluch (2013)
The hidocarbonetos monoaromatic BTEX (benzene, toluene, ethylbenzene and xylenes) have been used as solvents and are present in the environment, including air, soil and water. Among the most toxic components are benzene and toluene. For a correct evaluation of the effect of these contaminants in water is essential to carry out ecotoxicological studies. The objective of this work was to study the acute and chronic toxicity of monoaromatic hydrocarbons BTEX represented by tests on organisms Daphnia magna, Vibrio fischeri, Desmodesmus subspicatus and compare with the current laws. Aqueous solutions were prepared in the presence of methanol from patterns of BTEX-Mix, benzene, and toluene (isolated). These solutions were used to ecotoxicity tests according to standard procedures by ABNT. The results showed that in tests with Daphnia magna EC50 values (48h) for BTEX (mix), benzene and toluene were respectively 1187.27 μgL-1, 73.23 μgL-1, 81.58 μgL-1. Tests with Desmodesmus subspicatus showed no sensitivity to the BTEX (mix) until 1000 μgL-1 were obtained and the values of CI (96h) for benzene and toluene, respectively, 197.90 μgL-1, 7,270 μgL-1. With respect to the use of standardized methodologies been found that Daphnia magna assays showed higher reproducibility. The results of tests with Vibrio fischeri showed no reproducibility principally due to volatilization of the samples. Comparisons between the values of laws and the results obtained in tests enabled state that in most cases the maximum allowed values are below the EC50 found in the study. For disposal of effluent in the receiving body are disturbing the values stipulated when the receiver does not have great body ability to absorb the high loads of monoaromatic. For Ordinance number 2914/2011 of water amounts to 170 μgL-1. It is above the EC50 and EC10 found for Daphnia magna, while for tooth loss of animals as CONAMA 396/08 is below. The international environmental values coincide and are below the values found in the references already in Brazil for evaluation of liabilities are above.